Parental social isolation and child maltreatment risk during the COVID-19 pandemic - Lee, Shawna J. (Journal of family violence, 2022)
On March 11, 2020, COVID-19 was declared a pandemic by the World Health Organization. The social isolation and economic stress resulting from pandemic have the potential to exacerbate child abuse and neglect. This study examines the association of parents’ perceived social isolation and recent employment loss to risk for child maltreatment (neglect, verbal aggression, and physical punishment) in the early weeks of the pandemic. Participants (N = 283) were adults living in the U.S. who were parents of at least one child 0–12 years of age. Participants completed an online survey approximately 2 weeks after the World Health Organization declared that COVID-19 was a pandemic. The survey asked about recent changes (i.e., in the past 2 weeks) to employment status, parenting behaviors, use of discipline, use of spanking, and depressive symptoms. Nearly 20% of parents had hit or spanked their child in the past two weeks alone. Parents’ perceived social isolation and recent employment loss were associated with self-report of physical and emotional neglect and verbal aggression against the child, even after controlling for parental depressive symptoms, income, and sociodemographic factors. Parents’ perceived social isolation was associated with parental report of changes in discipline, specifically, using discipline and spanking more often in the past 2 weeks. Associations were robust to analyses that included two variables that assessed days spent social distancing and days spent in “lockdown.” Study results point to the need for mental health supports to parents and children to ameliorate the strain created by COVID-19.